PROBLEMS OF IMPLEMENTING GOVERNMENT POLICY REGARDING E-COMMERCE TRANSACTIONS WITH SOCIAL MEDIA PLATFORMS THROUGH MINISTER OF TRADE REGULATION NUMBER 31 OF 2023 - Muzdalifa Van Gobel; Asep Sumaryana; Didin Muhafidin (DIA: Jurnal Administrasi Publik, 2025)
This research aims to deepen our theoretical understanding of buying and selling activities through online platforms, specifically e-commerce. From a practical perspective, Indonesia lacks comprehensive laws and regulations concerning electronic transactions. This research will involve a qualitative approach centered on a literature review that examines books, literature, notes and reports relevant to the research problem. Researchers can access and utilize data directly without conducting fieldwork by leveraging existing library resources. The Peraturan Menteri Perdagangan Nomor 31 Tahun 2023 was enacted in response to concerns raised by local MSMEs about a decline in their business turnover due to the presence of TikTok Shop, a social-commerce platform. The government needs to continue to monitor and evaluate the implementation of this regulation and understand the impact between business actors and the government so that it becomes an effective tool to encourage growth and innovation in Indonesian digital trade. The contents of the Peraturan Menteri Perdagangan Nomor 31 Tahun 2023 concerning prohibiting TikTok Shop and other social media only from operating as online shop services are clear.